Growing weapons to fight hemophilia - Pier Mannuccio Mannucci (Bleeding, Thrombosis and Vascular Biology, 2023)
Very few rare diseases have witnessed the gigantic progress in patient care that took place for the hemophilias in the last 20 years. The first landmark was in the 1990s, when recombinant DNA technology afforded the industrial production, regulatory approval and commercialization of an array of factor VIII (FVIII) and factor IX (FIX) products, potentially available in unlimited quantity, efficacious and free from the risk of transmission of such bloodborne infections as HIV and the hepatitis virus B and C [...].